Bengal Muslims and colonial education, 1854-1947 : an imperiled agenda - Paul, Nilanjana (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book examines the impact of British education policies on the Muslims of Colonial Bengal. It evaluates the student composition and curriculum of various educational institutions for Muslims in Calcutta and Dacca to show how they produced the educated Muslim middle-class. The author studies the role of Muslim leaders such as Abdul Latif and Fazlul Huq in the spread of education among Muslims and looks at how segregation in education supported by the British fueled Muslim anxiety and separatism. The book analyses the conflict of interest between Hindus and Muslims over education and employment which strengthened growing Muslim solidarity and anti-Hindu feeling, eventually leading to the demand for a separate nation. It also discusses the experience of Muslim women at Sakhawat Memorial School, Lady Brabourne College, Eden College, Calcutta, and Dacca Universities at a time when several Brahmo and Hindu schools did not admit them. An important contribution to the study of colonial education in India, the book highlights the role of discriminatory colonial education policies and pedagogy in amplifying religious separatism. It will be useful for scholars and researchers of modern Indian history, religion, education, Partition studies, minority studies, imperialism, colonialism, and South Asian history"--
Conflict begins -- Partition politics -- Period of turmoil -- Fazlul Huq in power -- Girls' schools.
Keywords: Education -- India -- Bengal -- History -- 19th century; Education -- India -- Bengal -- History -- 20th century; Muslims -- Education -- India -- Bengal -- History -- 19th century; Muslims -- Education -- India -- Bengal -- History -- 20th century; Discrimination in education -- India -- Bengal -- History -- 19th century; Discrimination in education -- India -- Bengal -- History -- 20th century; Bangladesh -- History -- Autonomy and independence movements; HISTORY / Asia / India & South Asia; HISTORY / General; SOCIAL SCIENCE / General